2013
DOI: 10.1007/s10120-013-0306-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting peritoneal recurrence in advanced gastric cancer: implication for adjuvant intraperitoneal chemotherapy

Abstract: Background Despite adjuvant chemotherapy, patients with advanced gastric cancer (AGC) often develop recurrence, and the peritoneum is the most common site of recurrence. Therefore, intraperitoneal chemotherapy (IPC) has been proposed as a treatment option. The aim of this study was to select the eligible patients for application of IPC. The first site of recurrence was the peritoneum in 144 patients (58.8 %), and the 5-year peritoneal recurrence-free survival was 79.3 %. Depth of tumor invasion CT3, extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 29 publications
6
52
0
Order By: Relevance
“…Peritoneal recurrence was the most predominant failure pattern after D2 gastrectomy with adjuvant chemotherapy. These findings were congruent with those from previous studies, which indicated that adjuvant chemotherapy was effective but not sufficient to prevent peritoneal recurrence [16][17][18]. Because peritoneal recurrence has a detrimental effect on not only survival but also on quality of life, there is a growing interest in the development of novel adjuvant treatments for patients at high-risk for peritoneal recurrence [19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Peritoneal recurrence was the most predominant failure pattern after D2 gastrectomy with adjuvant chemotherapy. These findings were congruent with those from previous studies, which indicated that adjuvant chemotherapy was effective but not sufficient to prevent peritoneal recurrence [16][17][18]. Because peritoneal recurrence has a detrimental effect on not only survival but also on quality of life, there is a growing interest in the development of novel adjuvant treatments for patients at high-risk for peritoneal recurrence [19].…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, an upper body tumor, the presence of perineural invasion, diffuse type histology, T4, and advanced N stage (N2, N3a, and N3b) were all significant independent risk factors for peritoneal recurrence. These findings are congruent with those from previous studies [16,17]. However, by performing RPA on the above-mentioned factors, patients at risk of peritoneal recurrence could be grouped into two classes: high-risk (T4) and low-risk (T1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies showed no difference in prognosis between peritoneal recurrence and distant metastasis (8,25,26), the evaluation of risk factors for peritoneal recurrence and distant metastasis could improve selection of treatment and follow-up strategies. Depth of tumor invasion, lymph node metastasis, tumor size, Lauren classification diffuse type, undifferentiated cancer, and Bormann classification type 4 are independent risk factors for peritoneal recurrence (5,7,8,25,27,28). Meanwhile, depth of tumor invasion, lymph node metastasis, venous invasion, and Lauren classification intestinal type were determined to be independent risk factors for distant metastasis (5,8,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for peritoneal metastasis such as depth of tumor invasion and lymph node metastasis are related to high 18 F-FDG uptake (13,16,29). In contrast, tumors with diffuse type of Lauren classification and Bormann classification type 4 that show low 18 F-FDG uptake are also risk factors for peritoneal recurrence (5,7,9,13,21,28,31). Further, the high peritoneal recurrence rate in signet-ring cell carcinoma/ mucinous adenocarcinoma, which is known to have low 18 F-FDG uptake, could have contributed to the results of this study (9,13,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation